Effects of anti‐β2‐GPI antibodies on cytokine production in normal first‐trimester trophoblast cells. Issue 7 (20th April 2016) - Azuma, Hiromitsu; Yamamoto, Tatsuo; Chishima, Fumihisa
Abstract: Aim: The anti‐β2‐GPI antibody (aβ2‐GPIAb) has been detected in recurrent fetal loss with strong pathogenic activity. The effects of aβ2‐GPIAb on cytokine production and aβ2‐GPIAb binding sites in first‐trimester trophoblast cells were evaluated. Methods: First‐trimester trophoblast cells were cultured in 24‐well tissue culture plates with immunoglobulin G (IgG) obtained from aβ2‐GPIAb‐positive and aβ2‐GPIAb‐negative serum. Cytokines in the cultured supernatant were measured using the suspension array system and enzyme‐linked immunosorbent assays. To identify potential binding sites for aβ2‐GPIAb, such as toll‐like receptors (TLR) 2 or TLR4, we used mouse monoclonal anti‐TLR2 and/or anti‐TLR4 antibodies to inhibit TLR and then measured cytokine production. Results: The production of cytokines, such as interleukin‐6 and interleukin‐8, increased more in response to aβ2‐GPIAb‐positive IgG than to aβ2‐GPIAb‐negative IgG in trophoblast cells. The secretion of cytokines from trophoblast cells decreased when the TLR were blocked with mouse monoclonal anti‐TLR2 and anti‐TLR4 antibodies. Conclusion: We suspect that aβ2‐GPIAb might increase cytokine production by binding to TLR2 or TLR4. The increased cytokine production in response to aβ2‐GPIAb might play a role in the increased inflammatory response in the placenta.